PP-033 Stability study of 20 mg/ml paediatric amiodarone oral suspension in syrspend. (14th February 2016) - Quilliec, C; Bellay, R; Lesourd, F; Boivin, PN; Lester, MA; Gicquel, T
Abstract : Background: Amiodarone is a class 3 antiarrhythmic drug with a narrow therapeutic range. Absence of a paediatric formulation means the pharmacist has to produce a magistral preparation. Laboratory data show stability for amiodarone oral suspension at 5 mg/mL in Syrspend. However, this concentration is too low for important posologies. A more concentrated suspension is necessary (20 mg/mL). Purpose: The aim of this study was to determine the physicochemical stability of amiodarone oral suspension in order to have a shelf-life for the preparation of a maximum of 60 days. Material and methods: Three oral suspensions were prepared using amiodarone hydrochloride powder and Syrspend SF-PH4 (3 batches), packaged in amber vials to protect from light and stored at room temperature. Several parameters were studied on different days: 0, 3, 5, 8, 10, 15, 30 and 60 (n = 3): physical stability (visual inspection, osmolality measurements) and chemical stability (pH measurement, the concentration was analysed by a liquid chromatography-high resolution-mass spectrometer (LC-HR-MS)). Data were acquired in positive full scan mode and quantification was performed by extracting the exact mass value of protonated amiodarone (646.0302 m/z). Microbiological stability was observed by the test using colony counts on media platings. Results: After 60 days, no variation in pH or osmolality was observed. Once again, microbiological cultures were negative. Visual inspection showed viscosity increased after 10 days. The concentrations were the same until 10 days and then decreased from day 15 (40%). However, the degradation products were not tested and this work is under way. Conclusion: This study showed that 20 mg/mL amiodarone oral suspension in Syrspend at room temperature was stable for at least 10 days, so it has a shelf-life of 10 days. Additional studies will be undertaken to research the causes of the stability difference with the 5 mg/mL suspension. References and/or Acknowledgements: European Pharmacopoeia; Good manufacturing practices; International conference on harmonisation of technical requirements for registration of pharmaceuticals for human use; Methodological guidelines for stability studies of hospital pharmaceutical preparations, V Sautou et al, October 2013;74p No conflict of interest.